«Позбавлення прав» у демократичному суспільстві за романом Ельфріде Єлінек «Піаністка» - Кифор, Г. (Літературознавчі обрії. Праці молодих учених, 2010)
The article is based on the findings of the sociology of knowledge by Peter Bergmann and Thomas Lukman and on post-structural and deconstructive methods. The legitimating process of «exclusion» as the establishing of inter-structural violence in democratic society in the XX–XXI centuries is studied. The analysis reveals structural aspects of Elfriede Jelinek’s work.